Management and Long-term Outcomes of Giant Mediastinal Germ Cell Tumors in Children - Khanna, Kashish; Agarwala, Sandeep; Bishoi, Akshay Kumar; Bakhshi, Sameer; Bhatnagar, Veereshwar (Indian Journal of Medical and Paediatric Oncology, 2019)
Purpose: The purpose of the study is to evaluate the outcome of children with giant mediastinal germ cell tumors (GCTs). Materials and Methods: A retrospective study of children diagnosed with GCTs treated at our hospital from 1998 to 2014 was performed. They were evaluated for their tumor size, malignancy, treatment, complications, and outcome. Results: Twelve giant mediastinal GCT patients were included in the study. Age ranged from 7 to 144 months (median 12 months) and all except one were males. The average tumor size was 10.4 cm (range 6 cm × 5 cm–16 cm × 13 cm) and in four patients, they were large enough to occupy nearly the entire hemithorax. Nine children had benign tumors, and these were resected upfront. The remaining three cases with malignant disease received neoadjuvant chemotherapy. No significant reduction in size was noticed in these patients, but alpha-fetoprotein levels decreased in all the three, and they were later resected. Eight (67%) were resected through posterolateral thoracotomy and 4 (33%) through median sternotomy approach. One patient had a dumbbell-shaped thoracoabdominal tumor extending through a Bochdalek hernia. He required additional laparotomy as well as diaphragmatic repair. There were no postoperative complications. The malignant GCTs received total four courses of PEB. All patients were alive and asymptomatic at a mean follow-up of 55.4 months (range 10–146 months). Conclusions: Mediastinal GCTs have bimodal age distribution and show male preponderance. Malignant mediastinal GCTs responded well to neoadjuvant chemotherapy through a reduction in size was not noticed. Complete excision often in coordination with cardiothoracic-vascular surgeons can lead to long-term symptom-free survival even in giant tumors.
Keywords: Germ cell tumors; giant; mediastinum; outcomes; pediatric